The Ukrainian-Polish confrontation in Volhynia in the second world war: Historical memory transformations - Стрільчук, Людмила Василівна; Strilchuk, Liudmyla V. (Stefan cel Mare University of Suceava, 2018)
The conflict between Ukrainians and Poles in the period of the Second World War, known to the general public as „Volhynia tragedy/massacre”, is one of the most problematic and hotly debated issues of the common Polish-Ukrainian history. In recent years there have been a lot of controversial interpretations regarding the assessment of the causes and development of the conflict in Volhynia in 1943-1944, and especially the number of causalities of the conflict on both sides, including different approaches to presentation of the common history events. The problem in question has become the subject of political speculations, negatively affecting the inter-state relations, in general. The search for the ways to transform the historical memory of Ukrainians and Poles and to eliminate interethnic confrontations implies the multifaceted, unbiased elucidation of all aspects of the problem and surmounting the negative socio-historical stereotypes that occur in both societies.
Keywords: Ukrainians; Poles; confrontation; inter-ethnic conflict; World War II; historical memory